2022
DOI: 10.3390/medicina58121776
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Ankle Charcot Neuropathic Arthropathy after Spinal Surgery: A Case Report and Literature Review

Abstract: Charcot neuropathic arthropathy is a relatively rare, chronic disease that leads to joint destruction and reduced quality of life of patients. Early diagnosis of Charcot arthropathy is essential for a good outcome. However, the diagnosis is often based on the clinical course and longitudinal follow-up of patients is required. Charcot arthropathy is suspected in patients with suggestive symptoms and an underlying etiology. Failed spinal surgery is not a known cause of Charcot arthropathy. Herein we report a pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…Common causes include diabetes, syringomyelia, syphilis, spinal cord tuberculosis, spinal cord injury, leprosy, severe meningocele, intra-articular use of hormones, severe alcohol, amyloidosis and so on [ 4 ]. In addition, spinal surgery can also induce iatrogenic Charcot neuropathicarthropathy [ 5 ]. It has been reported that inflammation is particularly critical in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Common causes include diabetes, syringomyelia, syphilis, spinal cord tuberculosis, spinal cord injury, leprosy, severe meningocele, intra-articular use of hormones, severe alcohol, amyloidosis and so on [ 4 ]. In addition, spinal surgery can also induce iatrogenic Charcot neuropathicarthropathy [ 5 ]. It has been reported that inflammation is particularly critical in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%